Recent Advances in Catalysis Using Organoborane-Mediated Hydride Abstraction - Gillions, Joseph P.; Elsherbeni, Salma A.; Winfrey, Laura; Yun, Lei; Melen, Rebecca L.; Morrill, Louis C.; Pulis, Alexander P. (Synlett, 2023)
C–H functionalization is widely regarded as an important area in the development of synthetic methodology, enabling the design of more time- and atom-efficient syntheses. The ability of electron-deficient organoboranes to mediate hydride abstraction from α-amino C–H bonds is therefore of great interest, as the reactive iminium and hydridoborate moieties generated are able to participate in a range of synthetically useful transformations. In this review, we cover the recent advances made in organoborane-mediated hydride abstraction, and focus on the catalytic applications of electron-deficient boranes in α- or β-functionalization, α,β-difunctionalization, and the dehydrogenation of amines.1 Introduction2 α-Functionalization of Amines3 β-Functionalization of Amines4 α,β-Difunctionalization of Amines5 Dehydrogenation of Amines6 Summary and Future Prospects
Keywords: boron; hydride abstraction; amines; iminium; functionalization